DECOLONIAL FEMINISMS: A Transdisciplinary African Feminist Conversation (ICDL - Events by the GDO of the Cluster, 2022)
This Afro-Feminist Round Table will engage with decolonial feminism from francophone and anglophone African perspectives with a view to generating valuable insights in intersectional and decolonial epistemic frames pertinent to the Cluster’s agenda of reconfiguring African Studies. This intergenerational, transdisciplinary conversation has been is a sharing of thoughts and teachings from the speakers‘ diverse situated standpoints. Decolonial feminisms are epistemic frames to name and address all modes of systemic oppression. The conceptual tools implemented mobilize the knowledges produced by racialised women in the Global South throughout history, whereby transformative justice informs decolonial feminist visions. Knowledge production by racialised women has for the most part been about articulating life worlds and situated knowledges which have otherwise been consigned to the margins, dehumanised and/or erased. These knowledges form the bases of knowledge currently produced by Global South women scholars and activists working for much-needed transformative justice and life-affirming visions of futures. Moreover, decolonial feminism generate modes of care and hope as viable frams for envisioning African Futures for both established and early career scholars. Roundtable participants: Dr. Fatou Sow (sociologist and education scientist; Cheikh Anta Diop University, Dakar, Senegal and Centre National de Recherches Scientifique (CNRS) in Paris, France) Prof. Ousseina Alidou (African Literatures and Languages; Rutgers University, USA) Prof. Akosua Adomako Ampofo (sociologist, African and Gender Studies scholar; University of Legon, Accra, Ghana) Prof. Francoise Verges (political scientist and historian; Fondation Maison des sciences de l’homme, Paris, France) Chair: Dr. Christine Vogt-William, Director GDO, Africa Multiple Cluster of Excellence, University of Bayreuth The roundtable is designed as a pre-event for the award ceremony of the honorary doctorate for Dr. Fatou Sow later the same evening. It will be streamed online and may be attended via Zoom. ​ For more info please download the flyer. If you would like to join the event via zoom please register with africamultiple-gdo@uni-bayreuth.de